Debate de competencias jurídicas en el caso de “Jesús Santrich” : tratamiento noticioso de El Tiempo = Debate of legal competences in the case of "Jesús Santrich" : El Tiempo's news treatment (2018)
This article seeks to explain to what extent El Tiempo has contributed to the formation of a process of public deliberation regarding the capture of the FARC member, "Jesús Santrich", by investigating the news coverage that the media has given to the case of "Jesús Santrich". Santrich", by investigating the news coverage that the media gave to the judicial and political repercussions. It contextualizes who "Jesús Santrich" is, his role in the peace agreements in the framework of the peace accords, the background of his capture and investigation by the Prosecutor's by the Attorney General's Office and the DEA, and the judicial debate on the institutional competences in the case: the framing prioritized by the media. We followed up on 42 news items, two interviews and an editorial. 42 news items, two interviews and an editorial published by El Tiempo between April 9 and August 7, 2018, and August 7, 2018, which are analyzed in light of the standards of quality in the presentation of information and the role of the media in the the presentation of information and the role of the media in the construction of citizen deliberation in the construction of citizen deliberation in contemporary democracy